Interaction of fluxes of fast and thermal neutrons with an aqueous solution of organic dye methylene blue containing and not containing boric acid - Tsyats’ko, V.V.; Gokov, S.P.; Kazarinov, Yu.G. (Problems of Atomic Science and Technology, 2023)
The processes of interaction of neutron fluxes with an aqueous solution of the organic dye methylene blue (MB) – C₁₆H₁₈N₃SCl containing and not containing 4% boric acid (H₃BO₃) were studied. The work was carried out at the linear electron accelerator LUE-300 NSC KIPT. A set of tungsten plates was used as a neutron producing target. The electron energy was 15 MeV, the average current was 20 μA. The samples were behind lead shielding and without it, with and without a moderator. The energy spectra of neutron fluxes are calculated at the location of samples with a moderator with a thickness of 0 to 5 cm. The total neutron fluence was 2∙10¹¹ n/cm².